Radiative models for jets in X-ray binaries - Vila, Gabriela Soledad (2013)
In this work we develop a lepto-hadronic model for the electromagneticradiation from jets in microquasars with low-mass companionstars. We present general results as well as applications to somespecific systems, and carefully analyze the predictions of the model in thegamma-ray band. The results will be directly tested in the near futurewith the present and forthcoming space-borne and terrestrial gamma-ray telescopes.